Relationships among Contrasting Measurements of Microbial Dynamics in Pasture and Organic Farm Soils - S. L. Edenborn; A. J. Sexstone; Y. Sutanto; J. A. Chapman (Applied and Environmental Soil Science)
Soil bacteria exhibit short-term variations in community structure, providing an indication of anthropogenic disturbances. In this study, microbial biomass carbon (MBC), potentially mineralizable nitrogen (PMN), community level physiological profiling (CLPP), and culture-dependent DGGE (CD DGGE) fingerprinting of the 16S rRNA gene were used to compare microbial communities in organic farm and pasture soils subjected to differing agronomic treatments. Correlation analyses revealed significant relationships between MBC, PMN, and data derived from microbial community analyses. All measures separated soil types but varied in their ability to distinguish among treatments within a soil type. Overall, MBC, PMN, and CLPP were most responsive to compost and manure amendments, while CD DGGE resolved differences in legume cropping and inorganic fertilization. The results support the hypothesis that culturable soil bacteria are a responsive fraction of the total microbial community, sensitive to agronomic perturbations and amenable to further studies aimed at linking community structure with soil functions.